2021
DOI: 10.1108/idd-03-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

Clustering the countries for quantifying the status of Covid-19 through time series analysis

Abstract: Purpose This study aims to use financial stability and health facilities of countries, to cluster them for making a more consensus environment for manifesting the status of Covid-19 in a justifiable manner. The scarcity of the categorisation of the countries of the world in a common platform, and the requirement of manifesting the pandemic status such as Covid-19 in a justifiable manner create the demanding requirement. This study mainly focusses on assisting to generate a liable manifesto to criticise the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In the literature, some studies identified patterns of the Covid-19 impact in different countries [4][5][6][7][8]. Other works have used clusters to analyze the Covid-19 impact on counties across the United States [9][10][11].…”
Section: Sociodemographic Factors Associated Withmentioning
confidence: 99%
“…In the literature, some studies identified patterns of the Covid-19 impact in different countries [4][5][6][7][8]. Other works have used clusters to analyze the Covid-19 impact on counties across the United States [9][10][11].…”
Section: Sociodemographic Factors Associated Withmentioning
confidence: 99%